Phytotechnology: Macrophyte as phytoindicatot for unhealthy environment - Shaharuddin, Ruhul Izzati; Wan Muhamad, Wan Naimatul Asiah; Tukiman, Izawati; Othman, Rashidi (2010)
Aquatic plants or macrophytes are beneficial to fresh water bodies because they produce oxygen, which assists with overall fresh water bodies functioning, and provide food and shelter for aquatic living organisms. A lack of aquatic plants in a freshwater bodies system where they are expected to occur may suggest a reduced population of macro and micro fauna. In addition, the absence of aquatic plants may also indicate water quality problems as a result of excessive turbidity, herbicides, or salinization. However, an overabundance of aquatic plants can result from high nutrient levels and may interfere with freshwater bodies processing, recreational activities and detract from the aesthetic appeal of the system. The important of aquatic plants are eminent; they increase productivity of aquatic ecosystem and thus help to maintain ecosystem balance. Therefore aquatic plants are excellent indicators of unhealthy environment because they respond to nutrients, light, toxic contaminants, metals, herbicides, turbidity, water level change and salt. They also are integrators of environmental condition. Therefore the aim of this research is to study the potential of macrophytes as phytoindicator for excess nutrients. The abundance of Nelumbo nucifera, Eichhornia crassipes and Hydrilla verticillata were studied and observed at two different places at Kampar, Perak and Gombak, Selangor. At each site, 30 water samples were collected and analyzed for nitrite, nitrate, ammonium and phosphate. Eichhornia crassipes and Hydrilla verticillata were found to be substantially the best phytoindicator species for unhealthy environment specifically nitrogen and phosphorus contaminants. Meanwhile Nelumbo nucifera was found to be useful indicator of low level environmental contamination that might otherwise be difficult to detect. Therefore, from the results it can be concluded that all categories of aquatic plants (emerged, submerged and floater) can be manipulated as a tools to trace environmental contaminants of inorganic and organic pollutants.